HAEMATOLOGICAL ALTERATIONS IN HIV, MALARIA AND COINFECTED PATIENTS: A COMPARATIVE STUDY (FUDMA JOURNAL OF SCIENCES, 2025)
Blood parameters are typically altered in Human Immunodeficiency Virus (HIV) and malaria infections, and the extent of these alterations may vary due to several factors. These parameters can be used to determine the degree of damage resulting from the infections. The aim of this study was to assess changes in hematological parameters in individuals suffering from either malaria, HIV, or co-infection of both diseases. The study investigated haematological alterations in patients with HIV, malaria, and co-infection. HIV1/2 was screened using an immunochromatographic rapid test kit (DetermineTM HIV1/2), Total CD4 and CD3 cell counts were performed using the Partec flow cytometry, serum ascorbic acid was estimated by spectrophotometry, and the colorimeter method of Baker and Frank was used to determine Tocopherol (Vitamin E). The results showed that the mean ± SEM PCV, Hb, WBC, platelet, and neutrophil values of the HIV, malaria, and co-infected subjects were significantly lower (P
Keywords: Malaria; Haemoglobin; Lymphocytes; Tocopherol; Patients